Pembelajaran Kooperatif Mata Pelajaran PAI pada Masa Kurikulum Merdeka - Kahfi, Mas'ady Ashabul; Fahmi, Muhammad; Syaifuddin, Syaifuddin (An-Nuha, 2025)
Educational transformation through the Merdeka Curriculum requires a student-centered, collaborative, and differentiated learning model. This study aims to describe the application of cooperative learning models (STAD, TGT, Jigsaw) in Islamic Religious Education at SMP Negeri 1 Waru. The research used a descriptive qualitative approach with observation, interview, and documentation techniques, as well as Miles & Huberman's data analysis model. The results showed that the learning planning was in line with the principles of the Merdeka Curriculum through the preparation of ATP, teaching modules, and differentiated assessments. The implementation of the cooperative model encouraged active participation, improved conceptual understanding, and shaped attitudes of tolerance and communication skills. Student responses were generally positive, although there were challenges in the form of time management and unequal group participation. The conclusion of this study confirms that the application of cooperative learning models is relevant and effective in supporting the Merdeka Curriculum, while also contributing to the strengthening of the Pancasila student profile.